Factors Affecting the Self-ability of Cattle Farmers in Bioindustrial Agriculture in Jambi Province - Idris, Nahri; Muljono, Pudji; Mulyandari, Retno Sri Hartati; Jayanegara, Anuraga (Universitas Halu Oleo, 2022)
ABSTRACTThe aim of this study was to analyze the level of self-ability of cattle farmers in bio-industrial agriculture based on the cattle-oil palm integration, and also to determine the factors influencing the self-ability. A total of 225 respondents from cattle farmers were selected as respondents using a multistage cluster random sampling technique. The level of self-ability of farmers was measured by a scoring system based on the five principles of beef cattle farms. Data analysis employed the multiple linear regression analysis. Results indicated that the self-ability of cattle farmers in the study area was categorized as moderate. The self-ability indicator in the high category was feed, and the indicator in the low category was cattle breed. Self-ability in terms of management and production facilities, prevention and treatment of disease, and marketing was in the moderate category. The level of self-ability of cattle farmers was affected significantly by the experience of raising cattle, the level of income, and the activities of farmers in farmer groups. The policy implication is the stock of cattle breed is easy to obtain by farmers, facilitating access to capital and empowering farmer groups.Keywords: bioindustry, cattle, farmer group, integration, oil palm